Migratory status and movements of the portuguese mallard (Anas platyrhynchos) - Fabião, António (2000)
Results from recoveries, recaptures and resightings indicated a resident character of the portuguese mallard populations. Some winter migration may reach the studied areas but movements from the summer-ringed birds showed mostly dispersion and abmigration, although some were as long as 3580 km long until Russia. Frequent movements between local portuguese mallard populations resulted from dispersion.